Using DNA from hairs left at depredated greater sage‐grouse nests to detect mammalian nest predators - Christopher P. Kirol; Kristine L. Pilgrim; Andrew L. Sutphin; Thomas L. Maechtle (Wildlife Society Bulletin)
ABSTRACT Despite a multitude of studies on sage‐grouse (Centrocercus spp.), there is still sparse information on the predator communities that influence sage‐grouse productivity and how these predator communities may change when sagebrush habitats are altered by human activities. As a proof‐of‐concept, we used mammalian hairs collected at depredated greater sage‐grouse (C. urophasianus) nests and mitochondrial DNA sequencing to identify mammalian species that deposited the hairs at the depredated nests. We monitored nests of radiomarked female greater sage‐grouse in an oil and gas development area in the Powder River Basin, Wyoming, USA, from 2009 to 2011. We collected mammalian hair samples from 56 depredated nests. We detected 5 species: American badger (Taxidea taxus), bobcat (Lynx rufus), coyote (Canis latrans), red fox (Vulpes vulpes), and striped skunk (Mephitis mephitis). Red fox and striped skunk are considered exotic predators—species outside of their historical range—in our study area and represented 20% of our detections. This method could be improved by gathering and analyzing various types of DNA sources including predator saliva from egg shell fragments, predator scat, and even feathers left by avian predators. Our results suggest that this method has merit as a noninvasive tool to better understand the community of mammalian nest predators present within large study areas, and role of exotic predators in sagebrush habitats. © 2018 The Wildlife Society.